A translation re‐initiation variant in KLHL24 also causes epidermolysis bullosa simplex and dilated cardiomyopathy via intermediate filament degradation. (9th September 2022) - Vermeer, Mathilde C.S.C.; Al‐Shinnag, Mohammad; Silljé, Herman H.W.; Gaytan, Antonio Esquivel; Murrell, Dedee F.; McGaughran, Julie; Melbourne, Wei; Cowan, Timothy; van den Akker, Peter C.; van Spaendonck‐Zwarts, Karin Y.; van der Meer, Peter; Bolling, Maria C.
Abstract : This study shows that gain‐of‐function variants in KLHL24 causing EBS and DCM, do not only originate in the start‐codon and suggest that any nonsense‐inducing variant affecting nucleotides c.4_84 will likely cause the same effect on protein level and a similar potential lethal phenotype.